Appointments for vaccinations – restoring fairness and avoiding black markets - Dorothea Kübler; Rustamdjan Hakimov (WZB Berlin Social Science Center, 2021)
Booking an appointment for a Covid vaccination is tedious und like getting a ticket for the Olympic Games or a Lady Gaga concert, Those who currently hunt for appointments are 80 years and older. Rustamdjan Hakimov and Dorothea Kübler on restoring fairness and avoiding black markets.
Keywords: 300; COVID-19; Coronavirus; contagious disease; epidemic; vaccination; black market; elderly; Federal Republic of Germany